Surgical treatment of spinal tenosynovial giant cell tumor: Experience from a single center and literature review - Cao, Shiliang; Jiang, Liang; Yang, Shaomin; Liu, Zhongjun; Wei, Feng; Liu, Xiaoguang (Frontiers in Oncology, 2023)
Spinal tenosynovial giant cell tumor (TGCT) is a rare benign primary spinal tumor with aggressive behavior. The treatment strategy and prognosis of spinal TGCT remain unclear. This retrospective study aimed to evaluate the effectiveness of surgical treatment of spinal TGCT. We enrolled 18 patients with spinal TGCT who underwent surgical treatment in our hospital between January 2002 and January 2021. Additionally, we reviewed 72 cases of spinal TGCT with surgical treatment reported in the previous literature. Therefore, a total of 90 cases of spinal TGCT were evaluated for their clinical characteristics, surgical details, radiotherapy, and prognosis. In terms of the extent of resection, 73 cases (81.1%) underwent gross total resection (GTR), and 17 cases (18.9%) underwent subtotal resection (STR). Regarding the technique of GTR, 12 cases (16.7%) underwent en bloc resection, while 60 cases (83.3%) underwent piecemeal resection. During a median follow-up duration of 36 months (range: 3–528 months), 17.8% (16/90) cases experienced local recurrence/progression. The local recurrence/progression rate in cases that underwent GTR was 8.2% (6/73), which was significantly lower than that in cases with STR (58.8%, 10/17) (p＜0.001). The local recurrence/progression rate of en bloc resection was 8.3% (1/12), and that of piecemeal resection was 8.3% (5/60). Twelve cases underwent perioperative adjuvant radiotherapy, and one (8.3%, 1/12) of them showed disease progression during follow-up. Six recurrent/progressive lesions were given radiotherapy and all of them remained stable in the subsequent follow-up. Eight recurrent/progressive lesions were only treated with re-operation without radiotherapy, and half of them (50.0%, 4/8) demonstrated repeated recurrence/progression in the subsequent follow-up. Surgical treatment could be effective for spinal TGCT cases, and GTR is the preferred surgical strategy. Piecemeal resection may be appropriate for spinal TGCT cases with an acceptable local recurrence/progression rate. Perioperative adjuvant radiotherapy may reduce the risk of postoperative local recurrence/progression, and radiotherapy plays an important role in the treatment of recurrent/unresectable spinal TGCT lesions.